2018
DOI: 10.1186/s12879-018-3398-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Streptococcus pneumoniae strains in children with acute otitis media– high risk of persistent colonization after treatment

Abstract: BackgroundDespite advances in the development of pneumococcal conjugate vaccines, acute otitis media (AOM) is a common childhood infection, caused mainly by Streptococcus pneumoniae. It has been suggested that persistence of pneumococcal nasopharyngeal carriage is a risk factor for subsequent recurrent infections.MethodsIn this study we evaluate the relationship between 55 pneumococcal strains obtained from nasopharynx/oropharynx (NP/OP) and middle ear fluid (MEF) of 62 children, aged between 1 and 16 years, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
1
22
0
7
Order By: Relevance
“…In addition to being the most common reason for doctor's office visits among children, AOM is also currently the most common reason for antibiotic use in the pediatric population. Recent studies have shown antibiotic resistance and decreased sensitivity developing among the major otopathogens (Pichichero, 2000a;Zielnik-Jurkiewicz and Bielicka, 2015;Sillanpaa et al, 2016;Korona-Glowniak et al, 2018). Further, the polymicrobial biofilms associated with AOM are incredibly resistant and difficult to treat using classic antibiotic protocols (Pichichero, 2000b;Leibovitz et al, 2003;Libson et al, 2005;Asher et al, 2008;Leibovitz, 2008;Korona-Glowniak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to being the most common reason for doctor's office visits among children, AOM is also currently the most common reason for antibiotic use in the pediatric population. Recent studies have shown antibiotic resistance and decreased sensitivity developing among the major otopathogens (Pichichero, 2000a;Zielnik-Jurkiewicz and Bielicka, 2015;Sillanpaa et al, 2016;Korona-Glowniak et al, 2018). Further, the polymicrobial biofilms associated with AOM are incredibly resistant and difficult to treat using classic antibiotic protocols (Pichichero, 2000b;Leibovitz et al, 2003;Libson et al, 2005;Asher et al, 2008;Leibovitz, 2008;Korona-Glowniak et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobials inhibiting normal cells are made ineffective due to bacteria in biofilms growing slowly under nutrient- and aeration-depleted conditions (Davies, 2003). Resistance against commonly used antibiotics hampers treatment options (Korona-Glowniak et al, 2018). Consequently, new safe antimicrobials or antibiofilm agents that limit emergence of antibiotic-resistant bacteria are needed (Hurdle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Significant work was published in the last four years that focused on antibiotic resistance of S. pneumoniae. Several studies investigated the antibiotic and antimicrobial susceptibility of clinical isolates from multiple countries around the globe, these included Japan [35], Australia [36], Poland [37], Malaysia [38] and China [39]. Yang et al further investigated the specific effects of vancomycin treatment of S. pneumoniae via proteomic analysis [40].…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%